LEVEL AND FREQUENCY OF KNOWLEDGE OF POSTGRADUATE RESIDENTS IN BREAKING BAD NEWS TO THE PATIENTS IN A TERTIARY CARE HOSPITAL, KARACHI (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the level of knowledge of postgraduate residents in breaking bad news to the patients in a tertiary care hospital, Karachi.METHODOLOGY: This multicenter cross-sectional study design was conducted in 15th January to 15th april 2025 within the Anesthesia Department of Civil Hospital, Karachi, involving the participation of 140 postgraduate residents from a variety of governmental and private training institutions. In Karachi the study was approved by institutional review board, Dow University of Health Sciences (IRB-3775/DUHS/2024/27). After written informed consent eligible participants, aged between 24 and 40 years, representing both genders, were incorporated to evaluate the extent and prevalence of knowledge pertaining to the communication of adverse news among postgraduate anesthesia residents. The dataset was subjected to analysis via SPSS version 26, utilizing both descriptive statistics and the Chi-square test for comprehensive assessment.RESULTS: The mean age of the participants was 28.42 years (± 1.92 SD). Females were dominant (73.6%) while males were (26.4%). In the last six months, 87.1% of participants had broken bad news 1–24 times, while 12.9% had done so more than 24 times. The level of knowledge was determined as good (55.71%) and poor (44.29%). CONCLUSION: Although postgraduate residents frequently engage in the delivery of adverse news, a noteworthy fraction exhibited inadequate comprehension in this domain. These results underscore the necessity for the implementation of organized communication training, encompassing the SPIKES protocol, within residency curricula to improve residents' proficiency and facilitate patient-centered care.